2008
DOI: 10.1002/jor.20691
|View full text |Cite
|
Sign up to set email alerts
|

Autologous nucleus pulposus primes T cells to develop into interleukin‐4‐producing effector cells: An experimental study on the autoimmune properties of nucleus pulposus

Abstract: An autoimmune response to herniated nucleus pulposus has been proposed to constitute a pathophysiologic mechanism for inducing sciatica based on the fact that nucleus pulposus under normal conditions is excluded from the development of immunological tolerance. The manifestation of an autoimmune response comprises different steps starting with antigen capture, continuing with activation of T helper (T H ) cells and ending with production of autoantibodies. Activated T H cells differentiate into either T H 1 cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 38 publications
1
42
0
Order By: Relevance
“…Macrophages and NK cells, but not T cells, were detected, although the presence of T and B cells in isolated human herniated discs and in experimental porcine models has been previously reported (Geiss et al, 2007). Our results suggest an early immunological response after normal NP tissues were exposed to the immune system.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…Macrophages and NK cells, but not T cells, were detected, although the presence of T and B cells in isolated human herniated discs and in experimental porcine models has been previously reported (Geiss et al, 2007). Our results suggest an early immunological response after normal NP tissues were exposed to the immune system.…”
Section: Discussionsupporting
confidence: 48%
“…Nachemson (1969) reported decreased pH levels within and around a herniated lumbar disc and speculated that sciatica was caused by an inflammatory reaction surrounding the nerve root. Subsequently, various inflammatory chemical factors secreted from herniated NP, including tumor necrosis factor (TNF)-α (Weiler et al, 2005;Le Maitre et al, 2007), interleukin (IL)-1β (Le Maitre et al, 2007) and nitric oxide (NO) (Katsuno et al, 2008), have been implicated as causes of sciatica (McCarron et al, 1987;Geiss et al, 2007). Further, the production of matrix metalloproteinases (MMPs) has been implicated in the resorption of the herniated NP (Doita et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports have stated that herniated nucleus pulposus could be related to autoimmune response (4,5). The nucleus pulposus is an immune-privileged site because it is avascular and is thus excluded from immune surveillance.…”
Section: To the Editormentioning
confidence: 99%
“…Given the location of the sympathetic nerve trunk being immediately anterior to the lumbar spine, it is logical that these nerves might be affected by NP leakage caused by anterior disc herniation. Nonetheless, anterior herniation is seldom considered as one of the sources of sympathetic nerve-related syndromes, despite many studies having confirmed a sympathetic pain pathway [8][9][10][11] . Therefore, there is a possibility that anterior herniation of the lumbar discs may induce sympathetic inflammatory pain.…”
Section: Introductionmentioning
confidence: 99%